Extracorporeal Membrane Oxygenation as Life Support in Neonatal Respiratory Failure: A Single-Center Cohort Study and a Systematic Review - Raffaele Falsaperla; Rosanna Zanai; Ausilia Desiree Collotta; Vincenzo Sortino; Giovanna Vitaliti; Carla Cimino; Bruna Scalia; Marco Simone Vaccalluzzo; Michela Spatuzza; Grete Francesca Privitera; Alfredo Pulvirenti; Piero Pavone; et al. (Children)
Background: Extracorporeal membrane oxygenation (ECMO) is a life support in newborns with severe respiratory failure. Our main objective was to evaluate the mortality of patients and define positive and negative predictive factors of survival. Methods: We performed a Strengthening the Reporting of Observational Studies in Epidemiology (STROBE)-conformed retrospective observational study and a systematic review, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Our data were analyzed using R (v.4.2.1). We performed survival analysis, correlation analysis, and Fisher’s exact test. The first endpoint was the mortality rate. The second endpoint was to evaluate all factors associated with survival. The third endpoint was focused on complications of ECMO. Results: Our study included 8 patients treated in our centers and 45 patients from the literature review. Survival was 79%. Positive predictive factors of survival were a length of ECMO of less than 10 days and male neonates, while prematurity and the presence of 2 complications were negative predictive factors. Conclusions: ECMO functions as life support, although mortality and morbidity risks are high.